Mathematical model of the processes of electron-beam cleaning of flue gas from SO2, NOX, PAHS, VOCS - Моргунов, Владимир Викторович; Файнштейн, Александр Львович; Шкилько, Анатолий Максимович (Eastern-European Journal of Enterprise Technologies, 2012)
A mathematical model of radiation-chemical processes occurring in the gas phase under electron-beam (EB) purification of flue gases was developed, taking into account the phenomena of condensation